Detecção de genes de entrotoxinas de Staphylococcus aureus e estafilococos coagulase negativos isolados de leite bovino e de tanques de refrigeração comunitários procedentes de pequenas propriedades da região de Bauru-SP - Lemos, Fabio Almeida de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed at the isolation of Staphylococcus aureus and coagulase-negative staphylococci, from bovine milk samples, associated with cases of subclinical mastitis detected in ten small properties from Bauru - SP. Also, determine the antimicrobial susceptibility of the agents isolated and to investigate the presence of enterotoxin gene and the mecA gene of oxacillin resistance from the bacterial strains, and milk samples from bulk tanks . Of 105 samples obtained, 55 ( 52.4 %) were coagulase positive staphylococcus (CPS) and 50 (47.6%) coagulase negative staphylococcus (CNS). Among the CPS, S. aureus was isolated in most cases, 48 ( 87.3 %). Of the 12 CNS species isolated, the most frequent were S. warneri, S. hyicus, both with 8 (16%) and S. xylosus 7 (14%) . The highest levels of antibiotics resistance were observed for the group of β - lactam antibiotics - penicillin 92.7% and ampicillin 90.9% CPS and ECN - 56 % and 52 % respectively. The greatest sensitivity of the CPS strains was to cephalexin, and for CNS isolates to enrofloxacin. From the cases of subclinical mastitis, genes encoding enterotoxins were found in, 17/142 (12%) . The sea gene was the most prevalent being detected in 11 ( 7.7 %). The seb gene was detected in five (3.5%) samples, and in one sec (0.7%). All were negative for sed gene. When we consider the results directly from cultures of Staphylococcus spp. isolated from subclinical mastitis, there was only the gene sec in 8/105 (7.6%).From these isolates of Staphylococcus spp., positive for sec 05/105 (4.8%) were CPS, (03 S. aureus and 02 S.intermedius) and 03/105 (2.8%) CNS, (01 S. xylosus, 01 S.hyicus and 01 S.lugdunensis). To sea, seb and sed samples were negative. Of the ten samples from the bulk tanks, 02/10 (20%) were positive for sea and 01/10 (10%) to seb. The mecA gene was detected in three strains of S. aureus, representing 6.2% of the total of 48 S. aureus strains isolated. The identification ...

O presente estudo teve como objetivo o isolamento de Staphylococcus aureus e estafilococos coagulase negativos (ECN), associados com casos de mastite subclínica, a partir de amostras de leite de 134 vacas, em dez pequenas propriedades leiteiras familiares, da região de Bauru - SP, determinar a susceptibilidade a antimicrobianos e investigar a presença de genes de enterotoxinas e do gene mecA de resistência à oxacilina, dos casos de mastite subclínica, a partir das cepas bacterianas isoladas do leite dos animais, e dos tanques de resfriamento. Isolaram se 105 amostras de Staphylococcus spp, sendo 55 (52,4%) estafilococos coagulase positivos (ECP) e 50 (47,6%) ECN. Entre os ECP, S.aureus foi isolado em 48 (87,3%) dos casos. Das 12 espécies de ECN isoladas, as mais freqüentes foram S. warneri, S. hyicus, e S. xylosus. Os maiores níveis de resistência, foram observados frente ao grupo dos beta-lactâmicos tanto para os ECP - 92,7% para penicilina e 90,9% para ampicilina, como para os ECN - 56% e 52% de resistência, respectivamente. Todas amostras de ECP foram sensíveis a cefalexina, e 96% dos isolados de ECN a enrofloxacina. Em relação a presença de genes codificadores de enterotoxinas, dos casos de mastite subclínica, 17/142 (12%) foi positiva para algum dos genes estudados. O gene sea foi o mais prevalente, sendo detectado em 11 (7,7%). O gene seb em 05 (3,5%) e o sec em 01 (0,7%) das amostras. Todas foram negativas para o gene sed. Dos Staphylococcus spp isolados das mastites subclínicas, houve detecção do gene sec em 8/105 (7,6%), sendo que cinco (4,7%) eram ECP, e três (2,8%) ECN. Das 10 amostras de leite dos tanques, duas (20%) foram positivas para sea e uma (10%) para seb. O gene mecA foi detectado em três cepas de S. aureus, (6,2%). A identificação de genes codificadores de enterotoxinas em casos de mastite subclínica e em tanques comunitários, sinalizam a importância do monitoramento destes agentes visando a...
Keywords: Staphylococcus aureus; Estafilococos; Bovino de leite; Enterotoxinas; Mastite; Diagnóstico microbiológico; Dairy cattle; Staphylococcus